The effect of family centered care on meeting parental information needs of ‎hospitalized children - Jaleh Zeinali; Seyedeh Noshaz Mirhaghjou; Mahshid Mirzaei; Fatemeh Alhani; Ehsan Kazem Nezhad Leili; Maryam Dehghani (Guilan University of Medical Sciences, 2012)
Introduction: Information about the nature of disease decreases the anxiety and unusual ‎behaviors of parents specially mothers, and reduces their problems in recurrence of disease, ‎which occurs in at least ‎‏30%‏‎ of cases. Parents want correct information about the status of ‎their hospitalized child and also want to be involved in their child s care and expect health ‎care providers to let them know about the expected changes that may occur in children s ‎physical condition. ‎ Objective: The present study aims to determine the effect of family centered care on meeting ‎parental information needs of hospitalized children. ‎ Methods: In this quasi experimental study, ‎‏76‏‎ mothers of hospitalized children admitted to ‎emergency ward of ‎‏17‏Shahrivar educational hospitals in Rasht were chosen by sequential ‎sampling and divided into two groups of experimental and control group. Informed consent ‎forms were given to selected mothers and after their agreement, family centered care was ‎performed for experimental group based on developed protocol with participation of mothers. ‎The control group received routine cares. ‎ Results: Research findings showed that the level of meeting parental needs for information ‎was ‎‏%21.1‏‎ in control group and % ‎‏81.6‏‎ in experimental group. The t-test (p< ‎‏0‏‎.‎‏0001‏‎ t=‎‏6.922‏‎ ‎df=‎‏74‏‎) showed significant difference between the two groups. ‎ Conclusion: According to the study results family centered care was effective on the level of ‎meeting parents need for information and also lead to its increase.‎